Effect of Adding Al2O3 on the Macrostructure of Friction Stir Welding Polypropylene Sheet - Dinda Clara; Frantisek Miksik; Bambang Kusharjanta; Triyono Triyono; Aniddya Salsabila Kurnia Putri (Mekanika)
In this study, an experimental investigation had been carried out to determine the effect of alumina (Al2O3) addition in joining Polypropylene. Polypropylene is a thermoplastic material used mostly as a non-metallic material. One of the joining methods that can be applied in Polypropylene is Friction Stir Welding (FSW). The use of Al2O3 as a filler was to modify the Polypropylene matrix's properties to improve the joint's quality. The Al2O3 powder with 99.9% purity was inserted along the Polypropylene plates in the groove. This research analyzed the role of adding Al2O3 and tool rotation speed concerning the joint's quality. The experiment was performed under different values of tool speed rotation (204 rpm, 356 rpm, 620 rpm, and 1140 rpm) and the presence or absence of the addition of alumina powder. Then, the joint's quality was visually observed by optical macroscopy at the top and cross-section view. From macroscopic observations, adding alumina could make the visual of the joint look better and result in minimum defects than the joint without alumina addition. Instead, the increasing tool speed rotation helped the distribution of alumina during the welding process.